2015
DOI: 10.1097/iop.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein Dye Disappearance Test

Abstract: All anatomically failed DCR showed a positive FDDT (100% sensitivity) in this series. The proposed paradigm offers a less invasive approach to post-DCR epiphora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The accuracy of a diagnostic test is given by the sensitivity, specificity, positive, and negative predictive values rates. 6 Comparing endoscopic Jones I test with ABT in the assessment of anatomical and functional success rates, the authors found similar PPV rates (both 100% in anatomical success; 88% Jones I test, and 90.4% ABT in functional success). These outcomes may indicate that ABT could substitute Jones I test on postoperative DCR assessment.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The accuracy of a diagnostic test is given by the sensitivity, specificity, positive, and negative predictive values rates. 6 Comparing endoscopic Jones I test with ABT in the assessment of anatomical and functional success rates, the authors found similar PPV rates (both 100% in anatomical success; 88% Jones I test, and 90.4% ABT in functional success). These outcomes may indicate that ABT could substitute Jones I test on postoperative DCR assessment.…”
Section: Discussionmentioning
confidence: 93%
“…However, it has been associated with some discomfort, pain, difficulty to perform in children, and some patients do not cooperate with the test. 6,10 Functional success is usually assessed using Munk criteria; Munk 0 or 1 may indicate favorable outcomes. 22 In 1961, Jones described a simple test of lacrimal drainage function that becomes one of the most used procedures to evaluate epiphora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure has, on average, been reported in less than 10% of the patients with previous DCR procedure, and further investigation is required in order to find out the reason. 9 , 10 Endoscopy (nasal endoscopy and or dacryoendoscopy) could be an important tool for such an investigation, similar to preoperative assessment of the LDS. More importantly, it is considered the best option for revision surgery because of direct observation of the ostium and addressing the nasal cavity problems.…”
Section: Lacrimal Drainage Systemmentioning
confidence: 99%
“…Functional failure after Dacryocystorhinostomy (DCR) results when patients persist to have symptoms of epiphora or discharge even though there is a patent Nasolacrimal duct (NLD) by irrigation test. DCR is a surgical procedure that involves the formation of a shunt for drainage of tears between the lacrimal sac and the nasal cavity, bypassing the NLD [1,2]. Dacryocystorhinostomy is a standard surgical intervention meant to treat blocked nasolacrimal ducts of nearly all causes.…”
Section: Introductionmentioning
confidence: 99%